THE MALAYSIAN JOURNAL OF COMPUTER SCIENCE: A BIBLIOMETRIC STUDY - Bakri, Aryati; Willett, Peter (Malaysian Journal of Library and Information Science, 2009)
This paper analyses publication and citation patterns in the Malaysian Journal of Computer Science (MJCS) from 1996-2006. The articles in MJCS are mostly written by Malaysian academics, with only limited inputs from international sources. Comparisons are made with the companion Malaysian Journal of Library and Information Science in terms of the type, number of references, length and numbers of authors for individual papers. Searches of Google Scholar showed that 53 MJCS articles attracted a total of 86 citations, of which 43 were self-citations.